Sevoflurane versus propofol on immediate postoperative cognitive dysfunction in patients undergoing cardiac surgery under cardiopulmonary bypass: a comparative analysis - Na Zhao; Rui Qin; Bin Liu; Dongmei Zhang (Journal of Cardiothoracic Surgery)
Abstract Objective This study aims to compare the effects of sevoflurane (SEV) and propofol (PRO) on postoperative cognitive dysfunction (POCD) in patients undergoing cardiac surgery (CS) under cardiopulmonary bypass (CPB), with a focus on evaluating the efficacy of these anesthetic agents in preventing POCD. Methods A total of 113 patients undergoing CS with CPB were grouped into two: PRO group (n = 58) and SEV group (n = 55). Baseline data, anesthesia effects (CPB duration, anesthesia time, respiratory recovery time, and anesthesia recovery time), Montreal Cognitive Assessment (MoCA) scores, POCD incidence, neurological function markers (NSE, S-100β, MMP9), and serum inflammatory markers (IL-6, IL-8, TNF-α) were analyzed. The study was conducted between March 2018 and May 2021. Results The PRO group showed significantly shorter anesthesia time (P < 0.05), respiratory recovery time (P < 0.05), and anesthesia recovery time (P < 0.05) compared to the SEV group. The postoperative MoCA score in the PRO group reduced markedly compared with the baseline, but still higher than that in the SEV group (P < 0.05). The incidence of POCD was significantly lower in the PRO group (5.17% vs. 27.27%, P = 0.001). The levels of NSE, S-100β, MMP9, IL-6, IL-8, and TNF-α were significantly elevated compared to baseline values, but still lower than those in the SEV group (P < 0.05 for all comparisons). Conclusion PRO is more effective than SEV in preventing POCD in patients undergoing CS with CPB. It provides superior anesthetic effects and offers better protection against neuronal damage and serum inflammation compared to SEV. Clinical trial number Not applicable.